DETECTION OF MYCOBACTERIUM BOVIS IN BUFFALOES BLOOD THROUGH POLYMERASE CHAIN REACTION (PCR ) AND TUBERCULIN TEST - A. Khan; Z. I. Chaudhry; A. R. Shakoori; N. Mahmood; M. Ijaz; M. Z. U. Khan; Saima; I. Jan; M. M. Ali (Journal of Animal and Plant Sciences, 2012)
A study was conducted in buffaloes to detect the M. bovis in blood samples through PCR. The PCR assay was described which could detect M. bovis infection in blood samples that were apparently negative in PPD of tubercle bacilli. A total of 100 buffaloes blood samples were tested and 2.0 % buffaloes were found positive for M. bovis infection through single comparative cervical intradermal tuberculin test (SCCIDTT) while 54 % were found positive for M. bovis infection through PCR. The positive cases were analyzed in the background of their history. History revealed that these positive buffaloes were reared in a populated herd for a long time. This study provides an evidence of bovine tuberculosis caused by M. bovis in buffaloes which are main source of milk and meat is South Asia.
Keywords: bovine tuberculosis; buffaloes; prevalence; tuberculin test; PCR.